Rancang Bangun Aplikasi Location Based Service Butik Berbasis Android - Munir, Agus Q; Setyoningsih, Harum (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2018)
Yogyakarta was one of Indonesian tourist destinations that had potentials from its art and cultural interest. This was indeed supported mode development that was also one of art-cultural forms. Along with the era development, it was established a mode appreciation in Yogyakarta namely a boutique. The intense of boutiques in Yogyakarta had become various modes created so that it sometimes made customers had difficulties to determine which boutique to visit. This kind of condition was not effective towards time, cost and employees. Therefore, it needed a technology that was able to help customers in selecting boutiques. The study was designed and built using the Android mobile operating system is a variant of a mobile operating system developed from the Linux operating system. Android has a location-based service location-based service that is used to display and manipulate maps. Technology location based services using Android smartphone media can create applications that are useful in the selection of modes available in every boutique and facilitate the search location by using maps and routes that connect to the google map service. The results of this study are based apps location-based service boutique Android for the selection of boutique and can help facilitate in finding boutique location information.